ASH’ARISM IN NUSANTARA: Reviewing Traditional Ulama's Role in Shaping Islamic Creed in Nusantara - Noor, Umar Muhammad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2023)
Abstract: Since the beginning of the introduction of Islam in North-East Asia, Ash’arism has been represented Sunni theology that shaped the mainstream of Islamic belief in the region. However, during the last few years, it has been confronted serious contention from various parties. This article will examine the role played by its proponents in shaping Islamic belief and the challenges they faced to keep the tradition alive. It first briefly exposes how Ash’arism appeared and influenced theological discourse in various parts of Islamic world including Nusantara. Some prominent Nusantara ulamas and their contribution will be mentioned. Lastly, the study implies that although Ash’arism movement was challenged by a number of counterparts, it’s teachings and tenets nonetheless provide room and offer practical suggestions to keep it relevant to the current need.Keywords: Ash'arishm, Nusantara, traditional ulama, Islamic theology